Combining diffusion kurtosis imaging and clinical data for predicting the extramural venous invasion of rectal adenocarcinoma. Issue 148 (March 2022) - Chen, Weicui; Wei, Qiurong; Huang, Weikang; Chen, Jialiang; Hu, Shaowei; Lv, Xia; Mao, Liting; Liu, Bo; Zhou, Wu; Liu, Xian
Abstract: Objective: The aim of this study is to investigate the diagnostic ability of diffusion kurtosis imaging (DKI) -derived parameters combining with clinical data as risk factors for EMVI's involvement status in rectal adenocarcinoma. Materials and Methods: Preoperative MR examination including DKI and conventional diffusion-weighted imaging (DWI) was performed on 154 rectal adenocarcinoma patients enrolled in this respective study. Kmean, Dmean, and apparent diffusion coefficient (ADC) values were calculated. Clinical information, serum tumor markers, MR and pathological assessment of EMVI were recorded. The Shapiro-Wilk test, two-sample t -test, Mann-Whitney U test, Spearman's rank-order correlation, univariate and multivariate logistic regression analyses were used for statistical analysis. Receiver operating characteristic (ROC) curve analyses were performed to identify risk factors in EMVI involvement. Results: Of the 154 patients, pEMVI-positive rectal tumors had significantly higher Kmean values, lower ADCmean values compared to pEMVI-negative rectal tumors. Kmean values positively correlated with mrEMVI scores, whereas ADCmean values showed a negative correlation with mrEMVI scores. However, there was no significant correlation between the Dmean values and the mrEMVI scores. Univariate analysis demonstrated increased Kmean values, decreased ADCmean values, nodal involvement, an advanced tumor stage, and a G2 tumor grade were significantly related to the pEMVI of rectal adenocarcinoma. The multivariate analysis demonstrated that the Kmean values, lymph node involvement and an advanced tumor stage (T3) were independent risk factors for EMVI. Conclusion: The potential for diffusion kurtosis imaging as a biomarker for evaluating the EMVI of rectal cancer is feasible, especially given DKI's capability of detecting tumor heterogeneity noninvasively.